Treatment trajectories of gender incongruent Austrian youth seeking gender-affirming hormone therapy - Steininger, Jojo; Knaus, Sarah; Kaufmann, Ulrike; Ott, Johannes; Riedl, Stefan (Frontiers in Endocrinology, 2024)
The aim of this study was to describe the treatment trajectories of Austrian children and adolescents with gender incongruence seeking gender-affirming medical care.Methods: Patients who presented with gender incongruence at the pediatric outpatient clinic for differences in sex development at a large university hospital in Austria from January 2008 to December 2022 were included in a retrospective chart review, and analyzed regarding referral numbers, patient characteristics, treatment trajectories, fertility preservation, and legal gender marker changes.Results: Of 310 eligible patients, 230 (74.2%) were assigned female at birth (AFAB), and 80 (25.8%) were assigned male at birth (AMAB). The number of referrals increased steeply from 2008 to 2018, whereafter it stabilized at around 50 per year. At the time of initial presentation, the median age of patients was 15.6 years . AMAB individuals tended to be younger (median 14.9 years, IQR 13.9-16.8) than AFAB individuals (median 15.8 years, IQR 14.4-16.8; p= 0.012). 207 (66,8%) completed the assessment process and were eligible for gender affirming medical treatment (GAMT). Of those, 89% (186/207) commenced gender affirming hormone therapy in the pediatric outpatient clinic (79/186 received GnRHa monotherapy, 91/186 GnRHa and sex steroids, and 16/186 sex steroid monotherapy). Of the 54 AMAB individuals receiving GAMT, 6 (11.1%) completed fertility preservation prior to therapy initiation. Only 1/132 AFAB adolescent receiving GAMT completed fertility preservation. Chest masculinization surgery was performed in 22 cases (16.7%), and breast augmentation in two cases (3.7%) between the ages of 16 and 18. Changes in legal gender marker were common, with 205 individuals (66.1%) having changed their legal gender marker.This is the first time that treatment trajectories, fertility preservation rates, and changes of legal gender marker have been described in Austrian adolescents with gender incongruence seeking GAMT. The majority received GAMT and changed their legal gender marker, while gender affirming surgery rates were low, and utilization of fertility preservation treatment options was rare.